Baptist Political Theology - McKinney, Blake (Southwestern journal of theology, 2024)
Baptist Political Theology. Edited by Thomas S. Kidd, Paul D. Miller, and Andrew T. Walker. Brentwood, TN: B&H Academic, 2023. ix + 774 pp. $59.99.